(untitled) (Indian Journal of Child Health, 2021)
Background: This study is a review of recent research conducted in Egypt on the problem of rising prevalence rates of obesity among school-aged children. Methods: The search was conducted in three phases. The key words used were obesity, overweight, school-aged children, and nutritional status specifically for Egyptians over the past decade (2010–2021). Online research sites and the libraries of the Egyptian universities of the eluc.org. websites were searched along with on-site visits to the libraries of thesis universities and other research institutes in Egypt, to obtain full research material. Finally, retrieved data were analyzed statistically. Results: The search identified 24 studies that covered 15 governorates and one national survey that covered 25 governorates. The prevalence of obesity in the pooled populations was 10.6%. Prevalence rates of obesity were highest in Lower Egypt (LE) (10.0%) and urban governorates (9.2%) compared to Upper Egypt (UE) governorates (6.3%, p>0.05). Obesity in the children over 10 years was slightly higher among females in the urban (5.1%) and LE governorates (5.2%) compared to males (4.1 and 4.8%, respectively). However, it appeared higher in males (5.2%) compared to females (3.2%) in UE governorates (p>0.05). Conclusion: Obesity in Egypt is rising and is related primarily to high consumption of unhealthy foods. Member states must take active steps to regulate marketing of unhealthy foods to children.